2002
DOI: 10.1093/pcp/pcf085
|View full text |Cite
|
Sign up to set email alerts
|

BP-80 and Homologs are Concentrated on Post-Golgi, Probable Lytic Prevacuolar Compartments

Abstract: Prevacuolar compartments (PVCs) are membrane-bound organelles that mediate protein traffic between Golgi and vacuoles in the plant secretory pathway. Here we identify and define organelles as the lytic prevacuolar compartments in pea and tobacco cells using confocal immunofluorescence. We use five different antibodies specific for a vacuolar sorting receptor (VSR) BP-80 and its homologs to detect the location of VSR proteins. In addition, we use well-established Golgi-markers to identify Golgi organelles. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
129
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(141 citation statements)
references
References 54 publications
12
129
0
Order By: Relevance
“…A rhodamine-conjugated Fab fragment then was added and incubated at room temperature for 4 h before a second wash, followed by the addition of the second primary antibody. Additionally, we confirmed that the labeling pattern for an antibody used individually matched the pattern obtained with the same antibody when used in double labeling experiments (Jiang et al, 2000;Li et al, 2002). Secondary antibodies alone were also used as an additional control.…”
Section: Confocal Immunofluorescence Studiessupporting
confidence: 70%
See 3 more Smart Citations
“…A rhodamine-conjugated Fab fragment then was added and incubated at room temperature for 4 h before a second wash, followed by the addition of the second primary antibody. Additionally, we confirmed that the labeling pattern for an antibody used individually matched the pattern obtained with the same antibody when used in double labeling experiments (Jiang et al, 2000;Li et al, 2002). Secondary antibodies alone were also used as an additional control.…”
Section: Confocal Immunofluorescence Studiessupporting
confidence: 70%
“…Fixation and preparation of tobacco BY2 cells and their labeling and analysis by epifluorescence and confocal immunofluorescence have been described previously (Jiang and Rogers, 1998;Jiang et al, 2000;Li et al, 2002;Tse et al, 2004). The settings for collecting confocal images within the linear range were as described (Jiang and Rogers, 1998).…”
Section: Confocal Immunofluorescence Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Putative plant PVCs were identified using antibodies specific for the Arabidopsis (Arabidopsis thaliana) syntaxin Pep12p and the pea (Pisum sativum) vacuolar sorting receptor (VSR) BP-80 (Bassham et al, 1995;Conceicao et al, 1997;Paris et al, 1997). Studies on the relative distribution of VSR proteins between Golgi stacks and PVCs in various plant cells demonstrated that VSR proteins largely separated from Golgi markers and thus must be concentrated on PVCs under steady-state conditions (Li et al, 2002). In addition, a chimeric BP-80 reporter containing the BP-80 transmembrane domain and cytoplasmic tail colocalized with endogenous VSR proteins when the reporter was expressed in transgenic tobacco (Nicotiana tabacum) culture cells (Jiang and Rogers, 1998).…”
mentioning
confidence: 99%